In-vitro blockade of the CD4 receptor co-signal in antigen-specific T-cell stimulation cultures induces the outgrowth of potent CD4 independent T-cell effectors - Vatter, Sarah; Schmid, Maximilian; Gebhard, Claudia; Mirbeth, Carina; Klobuch, Sebastian; Rehli, Michael; Herr, Wolfgang; Thomas, Simone (Journal of Immunological Methods, 2018)
T-cell receptor (TCR) redirected T cells are promising tools for adoptive cancer immunotherapy. Since not only CD8 but also CD4 T cells are key players for efficient antitumor responses, the targeted redirection of both subsets with the same antigen-specific TCR comes more and more into focus. Although rapidly evolving technologies enable the reliable genetic re-programming of T cells, the limited availability of TCRs that induce T-cell activation in both T-cell subsets without CD4/CD8 co-receptor contribution hampers the broad application of this approach. We developed a novel stimulation approach, which drives the activation and proliferation of CD4 T-cell populations capable of inducing effector functions in a CD4-independent manner. Naive-enriched CD4 T cells were stimulated against dendritic cells (DC) expressing allogeneic HLA-DP antigens upon RNA transfection and CD4/HLA interactions were blocked by the addition of CD4 binding antibody. Evolving CD4 T-cell populations were specifically activated independent of the CD4 co-signal and induced strong TCR-mediated IFN-γ secretion as well as cytolysis upon recognition of leukemia cells expressing HLA-DP antigen. Our novel stimulation approach may facilitate the generation of CD4 T cells as source for co-receptor independent TCRs for future immunotherapies.
CRIS-Team Scopus Importer:2023-03-23
Keywords: CD4 co-receptor; CD4 T cells; HLA-DP; Immunotherapy; Leukemia; T-cell receptor